2006
DOI: 10.1121/1.2357716
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the homogeneous and forced solutions of a finite length, line-driven, submerged plate

Abstract: A formulation is developed to predict the vibration response of a finite length, submerged plate due to a line drive. The formulation starts by describing the fluid in terms of elliptic cylinder coordinates, which allows the fluid loading term to be expressed in terms of Mathieu functions. By moving the fluid loading term to the right-hand side of the equation, it is considered to be a force. The operator that remains on the left-hand side is the same as that of the in vacuo plate: a fourth-order, constant coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…That research showed that the tuning capabilities of simple RL shunt circuits were combined with the filtering characteristics of periodic structures to obtain a tunable periodic plate, and the resulting smart structure experienced significant reductions in its noise radiation capability. Numerical simulations demonstrated the applicability of Bloch theorem [5] for unit-cell analysis on the in vacuo plate [6] as a tool to predict the frequency ranges of effective structural acoustic control. Also, experiments were performed to validate the numerical predictions, and demonstrate the effectiveness of the proposed strategy.…”
Section: Introductionmentioning
confidence: 99%
“…That research showed that the tuning capabilities of simple RL shunt circuits were combined with the filtering characteristics of periodic structures to obtain a tunable periodic plate, and the resulting smart structure experienced significant reductions in its noise radiation capability. Numerical simulations demonstrated the applicability of Bloch theorem [5] for unit-cell analysis on the in vacuo plate [6] as a tool to predict the frequency ranges of effective structural acoustic control. Also, experiments were performed to validate the numerical predictions, and demonstrate the effectiveness of the proposed strategy.…”
Section: Introductionmentioning
confidence: 99%
“…That research showed that the tuning capabilities of simple RL shunt circuits were combined with filtering characteristics of periodic structures to obtain a tunable periodic plate, and the resultant smart structure experienced significant reductions in its noise radiation capability. Numerical simulations demonstrated the applicability of Bloch theorem [5] for unit-cell analysis on the in vacuo plate [6] as a tool to predict the frequency ranges of effective structural acoustic control. Also, experiments were performed to validate the numerical predictions, and to demonstrate the effectiveness of the proposed strategy.…”
Section: Introductionmentioning
confidence: 99%